Ethno-medicinal potentials and phytochemical properties of aloe vera: A review - Alara, John Adewole; Alara, Oluwaseun Ruth (Universiti Malaysia Pahang, 2019)
Aloe vera is a perennial ethno-medicinal potential plant with a xerophytic characteristic, but not a cactus. It has a famous history owing to its phytopharmaceutical properties and this had made it useful in the pharmaceutical, cosmetic and food industries. Studies had shown the positive effects of its extract against bacteria, fungi, virus and parasitic organisms. The phytochemical properties of A. vera have been exploited for various economic and commercial purposes. This review contributes literature on the bioactive potential composition, processing and the pharmaceutical potential uses, an adverse side-effect that might spring up in case of over dosage and important safety precautions are summarized. More scientific innovations and developments in the aspect of analytical chemistry are on the way to provide more acceptable, purified chemical characterization of A. vera using sophisticated laboratory equipment and machines.